If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 10p + 9 + 11 = -2(2p + 4) + -3(2p + -2) Reorder the terms: 9 + 11 + 10p = -2(2p + 4) + -3(2p + -2) Combine like terms: 9 + 11 = 20 20 + 10p = -2(2p + 4) + -3(2p + -2) Reorder the terms: 20 + 10p = -2(4 + 2p) + -3(2p + -2) 20 + 10p = (4 * -2 + 2p * -2) + -3(2p + -2) 20 + 10p = (-8 + -4p) + -3(2p + -2) Reorder the terms: 20 + 10p = -8 + -4p + -3(-2 + 2p) 20 + 10p = -8 + -4p + (-2 * -3 + 2p * -3) 20 + 10p = -8 + -4p + (6 + -6p) Reorder the terms: 20 + 10p = -8 + 6 + -4p + -6p Combine like terms: -8 + 6 = -2 20 + 10p = -2 + -4p + -6p Combine like terms: -4p + -6p = -10p 20 + 10p = -2 + -10p Solving 20 + 10p = -2 + -10p Solving for variable 'p'. Move all terms containing p to the left, all other terms to the right. Add '10p' to each side of the equation. 20 + 10p + 10p = -2 + -10p + 10p Combine like terms: 10p + 10p = 20p 20 + 20p = -2 + -10p + 10p Combine like terms: -10p + 10p = 0 20 + 20p = -2 + 0 20 + 20p = -2 Add '-20' to each side of the equation. 20 + -20 + 20p = -2 + -20 Combine like terms: 20 + -20 = 0 0 + 20p = -2 + -20 20p = -2 + -20 Combine like terms: -2 + -20 = -22 20p = -22 Divide each side by '20'. p = -1.1 Simplifying p = -1.1
| (x+3)2-4=0 | | 6n+12=78 | | -7=-7.5z-(-7z+3) | | log[4](2x-9)-log[4](x-8)=3 | | 3(x+9)=6x | | 2=x-4(2x+3) | | 8(r+2)=54 | | 7x=12x-45 | | (+15)+(-7)+(+1)= | | y=57-2 | | 2x+4x=3x+3 | | 3(x-9)=6x | | 1/5y=9-2/5y | | 4c-6=-2 | | 2n+5+4=-1 | | 4C-6=two | | xb=ya | | 2x=11+x | | 6x+1=6(x+1) | | Y=0.15x+0.55 | | 5(15+x)=-70 | | 2*5+8/2=18 | | 2.49+x= | | 9x+1/3x=0 | | 0.20(y-4)+0.16y=0.02y-0.07(60) | | 9x+3x=0 | | (4b+3b^4)-(2b-8b^4)+(5b+9b^2+6b^4)= | | 0.2m=0.3m+2.4 | | 16x^2+32x-65=0 | | m+33=112 | | -12+12=y | | 20-12=2x |